IMPLEMENTASI NILAI-NILAI KETELADAN NABI MUHAMMAD SAW DALAM POLA ASUH ANAK MUSLIM - Ainin Ditya; Amirah Syarifah Sirait; Ririn Widayanti; Masganti (Berajah Journal, 2025)
Parenting is the primary foundation for developing character, personality, and noble morals from an early age. From an Islamic perspective, the exemplary life of the Prophet Muhammad (peace be upon him) as a role model serves as an ideal reference for holistic parenting practices that combine spiritual, emotional, moral, and social dimensions. This article aims to examine the parenting principles applied in the life of the Prophet Muhammad (peace be upon him) and reflect them in the context of contemporary Muslim parenting. This research uses a qualitative approach with a literature review method, analyzing primary sources (the Qur'an and authentic hadith) and recent secondary literature. The results of the study indicate that the Prophet Muhammad (peace be upon him) implemented a parenting style full of compassion (rahmah), justice ('adl), gentleness, direct role modeling, and gradual and educative moral education. This approach is effective in preventing the formation of a negative inner child and shaping a generation with noble morals, empathy, and a Godly heart. The implementation of the Prophet's exemplary values ​​in modern parenting is not only relevant but also provides a humanistic and spiritual solution to address the challenges of parenting in the era of globalization.